The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s00300-007-0358-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiple origins of vagrant Subantarctic fur seals: a long journey to the Brazilian coast detected by molecular markers

Abstract: In this study, we present the first data about putative source populations of the vagrant Subantarctic fur seal, Arctocephalus tropicalis, found on the Brazilian coast, through the comparison of their mitochondrial DNA control sequences to exclusive haplotypes from the main breeding colonies of the species. The results indicated that, despite the majority of the vagrant individuals are from Gough Island (the closest breeding site to the Brazilian coast), they also come from other reproductive colonies, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…According to a study of the genetic variability in subantarctic fur seals encountered on southern Brazilian beaches, the vagrant specimens were derived from three reproductive colonies: Gough Island; Amsterdam Island; and the islands of Marion, Crozet and Macquarie (Ferreira et al, 2008). These vagrant individuals thus strayed widely off course before arriving on the Brazilian coast.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study of the genetic variability in subantarctic fur seals encountered on southern Brazilian beaches, the vagrant specimens were derived from three reproductive colonies: Gough Island; Amsterdam Island; and the islands of Marion, Crozet and Macquarie (Ferreira et al, 2008). These vagrant individuals thus strayed widely off course before arriving on the Brazilian coast.…”
Section: Discussionmentioning
confidence: 99%
“…Such results are therefore not representative of the whole diet of the far-ranging elephant seals in particular, and investigations using this technique were discontinued. Genetic profiling of the fur seal populations (Wynen et al 2000, Maboko et al 2007) and the elephant seal population (Chauke 2008) is underway, and provide additional information of long-range movements (de Bruyn et al 2007, Chauke 2008, Ferreira et al 2008, apart from tracking Bester 19998, de Bruyn et al 2009b, Tosh 2010) and tag recoveries (Bester 1989, Reisinger and.…”
Section: Current Research Focusmentioning
confidence: 99%
“…The intrusion of the Falkland/Malvinas Current appear to have an important role in the dispersal of the subantarctic fur seals as well as Antarctic fur seals found along the South American coast (Oliveira et al, 2001a), as shown in this paper. A recent genetic study comparing the A. tropicalis found on the Brazilian coast with animals from the main breeding colonies of this species indicated that despite the majority of the vagrants being from Gough Islands (40°20´S, 09°54´E), they could also come from other reproductive colonies (Ferreira et al, 2007). Furthermore, one vagrant individual which presented a DNA sequence matching an exclusive haplotype from the Crozet Islands (45°95´S, 50°33´E), probably moved west with assistance of the West Wind Drift, around the Antarctic and Falkland/Malvinas currents, reaching the Brazilian coast after covering a distance of about 16500Km.…”
Section: Introductionmentioning
confidence: 99%